Quality of life on caregiver of schizophrenia client in outpatient installation of Tampan psychiatric hospital - Patricia, Helena; Abdullah, Khatijah Lim; Erwina, Ira (International Journal Of Community Medicine And Public Health, 2019)
Background: The process of caring for a schizophrenic client creates a stressful situation; caregiver’s unpreparedness in dealing with this problem has an impact on the deterioration of the quality of life. The decline in quality of life of caregiver is influenced by several factors such as caregiver’s burden and characteristic of caregiver include age, gender, sex, marital status, education, income, and relationship with client. This study aimed to determine the relationship of burden and characteristic with the quality of life on the caregiver. Methods: The design of this study was descriptive analytic with cross sectional study approach on 186 caregiver with convenient technique sampling. Data were collected by the Zarit Burden Interview questionnaire and the World Health Organization Quality of Life (WHOQOL-BREF). Results: The results showed 99 (53.2%) caregivers had a low quality of life, 92 (49.5%) caregivers felt heavy burden. Chi-square statistical test proved a significant relationship between burden (0.001) and all characteristics caregiver include age (0.033), gender (0.033), sex (0.000) marital status (0.001), education (0.001), income (0.002), and relationship with client (0.000) with quality of life. Conclusions: The result showed that test proved a significant relationship between burden and characteristics caregiver with quality of life of multivariate analysis showed that marital status was the most correlated with quality of life of caregiver. Suggestions for Tampan Psychiatric Hospital Pekanbaru are to improve mental nursing service comprehensively to client and family like health education program about how to improve quality of life.